Mewujudkan UMKM Berkinerja Tinggi melalui Diversifikasi Produk dan Branding pada UMKM Babakaran Raos untuk Mencapai SDG’s No. 8 - Hariyanto, Wiwit; Hudi, Lukman; Hermawan, Sigit; Ahmad, Aufa; Miranda, Wiji Amelia (Universitas Muhammadiyah Mataram, 2026)
Abstract: Babakaran Raos MSME is a culinary business facing challenges in improving product quality, menu variety, and business competitiveness amidst increasingly fierce market competition. This Community Service (Abdimas) activity aims to create a quality MSME through product diversification strategies and strengthening business branding. The implementation method of the activity includes training and mentoring in the production of presto milkfish as a form of product diversification, business branding mentoring through improving visual identity and product packaging, and strengthening understanding of digital-based marketing. Abdimas activities are carried out in a participatory manner by prioritizing direct practice so that partners gain applicable experience in business development. The results of the activity show an increase in partner knowledge and skills in processing more varied, hygienic, and value-added products, as well as an increase in partner understanding of the importance of branding in building product image and appeal in the eyes of consumers. In addition, Babakaran Raos MSME has a diversified product, namely presto milkfish. This program is expected to be able to encourage the sustainability of Babakaran Raos MSME and become a model for MSME empowerment based on product quality improvement and branding strategies.Abstrak: UMKM Babakaran Raos merupakan usaha kuliner yang menghadapi tantangan dalam peningkatan kualitas produk, variasi menu, dan daya saing usaha di tengah persaingan pasar yang semakin ketat. Kegiatan Pengabdian kepada Masyarakat (Abdimas) ini bertujuan untuk mewujudkan UMKM yang berkualitas melalui strategi diversifikasi produk dan penguatan branding usaha. Metode pelaksanaan kegiatan meliputi pelatihan dan pendampingan produksi olahan bandeng presto sebagai bentuk diversifikasi produk, pendampingan branding usaha melalui perbaikan identitas visual dan kemasan produk, serta penguatan pemahaman pemasaran berbasis digital. Kegiatan Abdimas dilaksanakan secara partisipatif dengan mengedepankan praktik langsung agar mitra memperoleh pengalaman aplikatif dalam pengembangan usaha. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan keterampilan mitra dalam mengolah produk yang lebih variatif, higienis, dan bernilai tambah, serta meningkatnya pemahaman mitra terhadap pentingnya branding dalam membangun citra dan daya tarik produk di mata konsumen. Selain itu, UMKM Babakaran Raos telah memiliki produk diversifikasi yakni bandeng presto. Program ini diharapkan mampu mendorong keberlanjutan UMKM Babakaran Raos serta menjadi model pemberdayaan UMKM berbasis peningkatan kualitas produk dan strategi branding.